(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The research has been done for removing asphaltene by pickling process of diesel oil from pyrolysis oil self-made by waste rubber in this paper, and the study showed that pickling effect of concentrated sulfuric acid was better than concentrated hydrochloric acid. The best pickling effect was found when the concentration of sulfuric acid was 18.4mol/L, acid to oil ratio, namely, the amount of concentration of sulfuric acid to the amount of diesel oil ratio, was 25%. This experiment proved that removing asphaltene by pickling process using concentrated sulfuric acid was remarkable.